Virtual pollination trade uncovers global dependence on biodiversity of developing countries - Silva, Felipe Deodato da Silva e (2021)
Nations’ food consumption patterns are increasingly globalized and trade dependent. Natural resources used for agriculture (e.g., water, pollinators) are hence being virtually exchanged across countries. Inspired by the virtual water concept, we, herein, propose the concept of virtual biotic pollination flow as an indicator of countries’ mu- tual dependence on biodiversity-based ecosystem services and provide an online tool to visualize trade flow. Using information on 55 pollinator-dependent crop markets (2001–2015), we show that countries with higher development level demand high levels of biodiversity-based services to sustain their consumption patterns. Such patterns are supported by importation of virtual biotic pollination (up to 40% of national imports of pollinator- dependent crops) from developing countries, stimulating cropland expansion. Quantifying virtual pollination flow can help develop new global socioeconomic policies to meet the interconnected challenges of biodiversity loss, ecosystem health, and social justice.